Menarik Akar Sejarah Pendidikan Indonesia: Pancasila sebagai Fondasi Pembentukan Karakter Bangsa di Era Kontemporer - Ariwinata, Yuda; Ofianto, Ofianto (Lembaga Yasin AlSys, 2025)
Education in Indonesia has deep historical roots as a tool for liberation from colonialism and as a means of shaping national character, with Pancasila serving as both the state ideology and the primary philosophical foundation of the national education system. This article aims to examine the historical roots of Indonesian education, the central role of Pancasila in character formation, and the contemporary challenges in consistently and contextually integrating its values into the education system. Using a descriptive qualitative approach based on literature review, this study explores various academic sources and educational policies to identify how Pancasila values are embedded in the curriculum and educational practices in the modern era. The findings reveal that although Pancasila has been normatively established as the foundation of the national education system, its implementation continues to face obstacles such as gaps in understanding, policy inconsistency, and the pressures of globalization and digitalization. The study concludes that strengthening Pancasila values requires the development of a contextually relevant curriculum, improvement in teacher quality, and synergy among the government, educational institutions, and society. Revitalizing Pancasila-based character education emerges as a key strategy in shaping a generation that is intellectually competent as well as morally and socially resilient in navigating the complexities of the modern world.